2010
DOI: 10.5194/bg-7-3517-2010
|View full text |Cite
|
Sign up to set email alerts
|

McGill wetland model: evaluation of a peatland carbon simulator developed for global assessments

Abstract: Abstract.We developed the McGill Wetland Model (MWM) based on the general structure of the Peatland Carbon Simulator (PCARS) and the Canadian Terrestrial Ecosystem Model. Three major changes were made to PCARS: (1) the light use efficiency model of photosynthesis was replaced with a biogeochemical description of photosynthesis; (2) the description of autotrophic respiration was changed to be consistent with the formulation of photosynthesis; and (3) the cohort, multilayer soil respiration model was changed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 60 publications
4
123
1
Order By: Relevance
“…Work is underway to introduce a new moss plant functional type in CLM_SPRUCE, and we will use observations being gathered from the S1-Bog to parameterize the influence of water content on Sphagnum photosynthesis, and to better understand the influence of moss on hydrological and biogeochemical conditions in peatland bogs. Previous efforts at synthesizing and modeling moss physiology and physical properties are informing our progress in this area (St-Hilaire et al, 2010;Turetsky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work is underway to introduce a new moss plant functional type in CLM_SPRUCE, and we will use observations being gathered from the S1-Bog to parameterize the influence of water content on Sphagnum photosynthesis, and to better understand the influence of moss on hydrological and biogeochemical conditions in peatland bogs. Previous efforts at synthesizing and modeling moss physiology and physical properties are informing our progress in this area (St-Hilaire et al, 2010;Turetsky et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of hummock-hollow microtopography has important impacts on hydrological dynamics (Lindholm and Markkula, 1984;Verry et al, 2011b), nutrient availability (Chapin et al, 1979;Damman, 1978), plant species distribution and productivity (Andrus et al, 1983;Moore, 1989), and decomposition rates (Johnson and Damman, 1991). Many wetland ecosystem models drive biogeochemical simulations using observed water table depth as an input variable (St-Hilaire et al, 2010;Frolking et al, 2002;Hilbert et al, 2000). Even though such models include water table effects, the models have not simulated observed variation for hummock/hollow microtopography common to raised-dome bog peatlands.…”
Section: Introductionmentioning
confidence: 99%
“…The moss photosynthesis and dark respiration are calculated using the Farquhar (1989) biochemical approach following the MWM (St-Hilaire et al, 2010) and CTEM (Melton and Arora, 2016), with modifications for integration with CLASS-CTEM and moss phenology. The leaf-level gross photosynthesis rate G 0,m (µmol CO 2 m −2 s −1 ) is obtained as the minimum of the transportation limited photosynthesis rates (J s ) and the first root of the quadratic solution of the light-limited rate (J e ) and the Rubisco limited rate (J c ).…”
Section: Primary Production Of Mossesmentioning
confidence: 99%
“…On the other hand, several peatland models have been developed and evaluated for individual sites. For example, the McGill Wetland Model (MWM) simulates the C exchange in Degerö Stormyr and the Mer Bleue bog (St-Hilaire et al, 2010); the peatland version of the General Ecosystem Simulator -Model of Raw Humus, Moder and Mull (GUESS-ROMUL) simulates the variation of net ecosystem production (NEP) with water table position in a fen (Yurova et al, 2007); and the PEATBOG model simulates C and N cycles in peatlands, specifically the Mer Bleue bog ). These models have been shown to reproduce well the processes occurring in the peatlands that they were designed for.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the water table determines the separation of soil into a methane producing and a methane oxidising zone. While most studies identify wetlands as net carbon sinks for today's climate conditions (Bohn et al, 2007;Gorham, 1991;Friborg et al, 2003), a number of studies concluded that some wetlands might turn into carbon sources in a warmer climate (St-Hilaire et al, 2010;Gorham, 1991) due to higher productivity of methane releasing microbes.…”
Section: Introductionmentioning
confidence: 99%